Treatment of disorder eﬀects in X-ray absorption spectra beyond the conventional approach - Kuzmin, Alexei; Timoshenko, Janis; Kalinko, Aleksandr; Jonane, Inga; Anspoks, Andris (Elsevier Ltd., 2020)
The contribution of static and thermal disorder is one of the largest challenges for the accurate determination of the atomic structure from the extended X-ray absorption fine structure (EXAFS). Although there are a number of generally accepted approaches to solve this problem, which are widely used in the EXAFS data analysis, they often provide less accurate results when applied to outer coordination shells around the absorbing atom. In this case, the advanced techniques based on the molecular dynamics and reverse Monte Carlo simulations are known to be more appropriate: their strengths and weaknesses are reviewed here.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Extended X-ray absorption fine structure (EXAFS); Molecular dynamics; Reverse Monte Carlo; Static and thermal disorder; X-ray absorption spectrocopy